The anaesthetic management of patients undergoing caesarean section surgery and its impact on post-operative analgesia - Chetty, Sean (My University, 2016)
Poorly controlled pain following caesarean section surgery can have a debilitating effect on the physical and emotional well being of a woman during the post-operative period. Good intra-operative anaesthetic management during caesarean section surgery is requisite to improve post-operative analgesia, and thereby contribute to the well being of the patient. In South Africa (SA) there are currently no national obstetric anaesthesia practice guidelines. Anaesthetic service providers therefore rely on knowledge acquired during their anaesthetic training and recommendations from international guidelines (which may not be applicable in SA). In order to establish a reference standard of anaesthetic care for obstetric patients in SA, a semi-structured interview was conducted with the heads of department and/or their representatives from the eight anaesthesiology academic departments in SA in 2012. The experts provided recommendations on the intra-operative anaesthetic management of patients for elective and emergency caesarean sections, as well as the post-operative monitoring and analgesic management of these patients. The recommendations were based on the experts’ understanding of the uniquely local healthcare environment in SA. Following the establishment of the SA reference standard, a national survey of anaesthetic service providers was conducted in 2014 to establish what the practises are in South Africa for caesarean section anaesthetics. Ninehundred- and-thirty-three survey responses were analysed, which equated to a 58% response rate. The majority of anaesthesia providers (97.8%) perform single shot spinal anaesthesia for caesarean sections. Thirty percent of respondents chose to use Quincke spinal needles, despite the increased risk of this needle causing post-dural puncture headaches (PDPH). The preferred local anaesthetic drug was 0.5% bupivacaine with dextrose, and fentanyl was the most commonly used additive agent, as opposed to common international practice, which advocates morphine. The survey also revealed that 58% of doctors work in hospitals that do not have a post-operative monitoring protocol for patients following caesarean section surgery. This contrasts to recommendations suggested by the national experts regarding patient monitoring requirements. A clinical trial was then conducted to compare the analgesic efficacy of two different doses of intrathecal morphine (50μg and 100μg) with 25μg fentanyl. Patients in both morphine treatment groups had significantly lower postoperative opioid requirements than patients in the fentanyl group. The pain numerical rating scale (NRS) scores were however not statistically different and there was also no difference in the side effects profile or emotional parameters measured, between the groups. This study highlights the differences in the recommended practise of obstetric anaesthesia in SA compared to other countries and demonstrates how obstetric anaesthesia is practised in SA. The final component of this study has demonstrated how international best practices can be easily implemented in SA to improve the anaesthetic care of the obstetric patient.
A Thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. 14th October 2016 in Johannesburg
Keywords: Postoperative Period; Analgesia; Cesarean Section